Sensitivity Analysis of Risk from Stakeholders' Perception Case Study: Semarang-solo Highway Project Section I (Tembalang-Gedawang). (2015) - Nurdiana, Asri; Wibowo, M. Agung; Hatmoko, Jati Utomo D.
Abstract: Risks at construction are borned by some parties. Each party carries the risks in accordance to their respective and responsibilites in the project. In Semarang-Solo Highway Project Section 1 (Tembalang-Gedawang), which was built in 2010 until 2011, the risks are borned by each stakeholder in the project, such as contractor, owner, consultant of planning, supervisory consultant, and society around the area of the project. Probability and impact of risk in the project can be estimated by risk analysis for defining the priority of risk. The risks of each stakeholder may change dinamically as changes in the stakeholder, such as policy changes because of internal or external factors. These changes can be predicted by sensitivity analysis that predicts the changes of risk priority in a decisional hierarchy structure because of the changes in each stakeholder. The aims of this paper are to analyze all risks at the project and to analyze the sensitivity of risk at Semarang-Solo Highway Project Section 1 (Tembalang-Gedawang). Primary data were taken through the interview, then analyzed using AHP (Analythical Hierarchy Process) method. The respondents were the decision maker on related projects. Sensitivity analysis uses weight changes simulations at hierarchical structure with Analythical Hierarchy Process. This paper assessed the risk sensitivity analysis on the project Semarang-Solo Highway Project section I-Gedawang Tembalang, and it's found that the contractor, consultant of planning, and supervisory consultant, are sensitive to changes in some weight changes simulations. While the owner and the society are not sensitive to changes that occur.